2002
DOI: 10.1111/j.1095-8312.2002.tb01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and field experiments identify sources of variation in phenotypes and survival of hatchling lizards

Abstract: To understand the process of natural selection, relationships between phenotype and fitness and sources of phenotypic variation must be known. We examined the importance of incubation moisture conditions, maternal yolk investment, and clutch (genotype) to phenotypic variation in hatchlings of the lizard Sceloporus undulatus. Eggs were distributed among two moisture treatments and a third treatment in which yolk was removed. After hatching, mass, snout–vent length, tail length, body shape, thermal preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 61 publications
(86 reference statements)
3
91
0
1
Order By: Relevance
“…Although these effects of incubation temperature on the body size of hatchlings may influence offspring survival under field conditions (as proposed by hypothesis B), the magnitude of these effects in our study was so small (3-4% difference in body size) that we doubt they would have a significant impact on survival. For example, previous experiments on iguanid lizards where body size was greatly reduced (up to 20%) did not always influence rates of survival in the field (Sinervo et al 1992;Warner and Andrews 2002). Moreover, the effects of incubation temperature on hatchling morphology in our dragons were short lived and rapidly overwhelmed by differentials induced by environmental conditions post-hatching.…”
Section: Hypotheses B and C: Different Phenotypic Optima For Sons Vermentioning
confidence: 63%
“…Although these effects of incubation temperature on the body size of hatchlings may influence offspring survival under field conditions (as proposed by hypothesis B), the magnitude of these effects in our study was so small (3-4% difference in body size) that we doubt they would have a significant impact on survival. For example, previous experiments on iguanid lizards where body size was greatly reduced (up to 20%) did not always influence rates of survival in the field (Sinervo et al 1992;Warner and Andrews 2002). Moreover, the effects of incubation temperature on hatchling morphology in our dragons were short lived and rapidly overwhelmed by differentials induced by environmental conditions post-hatching.…”
Section: Hypotheses B and C: Different Phenotypic Optima For Sons Vermentioning
confidence: 63%
“…The cause of discrepancy in the results of these two studies is not clear. Also, in S. undulatus dry settings produced smaller hatchlings than those from wet settings (Warner and Andrews 2002). Recent study by Robbins and Warner (2010) reported that the incubation moisture regimes have an influence on posthatching growth in S. undulatus rather than on the size at hatching.…”
Section: Discussionmentioning
confidence: 94%
“…The soil moisture condition available during incubation is reported to influence hatchling size, growth, locomotor speed, and desiccation tolerance, and survival in different species of reptiles (Packard 1991, Finkler 1999, Brown and Shine 2005. In addition, it is known to influence the amount of yolk that is utilized by the developing embryos of Sceloporus undulatus (Warner and Andrews 2002). The previous studies analyzed the effects of moisture on hatchling phenotype by incubating the eggs partially buried in the substratum at constant temperature and moisture (Muth 1980, Packard 1999, Lin et al 2005, Finkler 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Risk-averse behavior and growth rate may be associated with fitness in reptiles (Sinervo and Adolph 1994;Cooper 1997;Warner and Andrews 2002;Martín et al 2003). These characteristics in offspring may be determined by the maternal signal during embryonic development.…”
Section: Do Gravid Females Become Selfish? Female Allocation Of Energmentioning
confidence: 99%